2017
DOI: 10.1111/rec.12624
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection of riparian birds at restoration sites along the Trinity River, California

Abstract: Riparian habitats in the western United States are imperiled, yet they support the highest bird diversity in arid regions, making them a conservation priority. Riparian restoration efforts can be enhanced by information on species response to variation in habitat features. We examined the habitat selection of four riparian birds known as management indicators at restoration and reference sites along the Trinity River, California. We compared vegetation structure and composition at nest sites, territories, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Structural vegetation complexity in meadow and other riparian systems enhances insect food resources (Ramey & Richardson 2017) and provides cover from direct and nest predation (Ammon & Stacey 1997). Tall willows in riparian areas are particularly attractive to many species we studied (Bombay et al 2003; Rockwell & Stephens 2018). Though increasing RDV may come with an apparent tradeoff of reduced abundance of one focal species—Wilson's Snipe, with possibly similar ramifications for Sandhill Crane which select open, inundated areas of meadows for nesting (Littlefield 1995)—restoring the RDV component of riparian meadows is critical to ensure positive outcomes for all other focal species.…”
Section: Discussionmentioning
confidence: 99%
“…Structural vegetation complexity in meadow and other riparian systems enhances insect food resources (Ramey & Richardson 2017) and provides cover from direct and nest predation (Ammon & Stacey 1997). Tall willows in riparian areas are particularly attractive to many species we studied (Bombay et al 2003; Rockwell & Stephens 2018). Though increasing RDV may come with an apparent tradeoff of reduced abundance of one focal species—Wilson's Snipe, with possibly similar ramifications for Sandhill Crane which select open, inundated areas of meadows for nesting (Littlefield 1995)—restoring the RDV component of riparian meadows is critical to ensure positive outcomes for all other focal species.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Schlossberg, King, Chandler, and Mazzei () concluded that bird‐preferred understory habitat could be separated into areas of tall shrub cover or low shrubs and forbs. Other studies show that some shrub‐nesting birds prefer sites with high woody stem density as predation defense (Rockwell & Stephens, ; Schill & Yahner, ; Stauffer & Best, ). As the ground‐foraging birds in our survey are almost entirely insect—consumers or omnivores, we suggest that ground‐foraging bird abundance may be due to the abundance and diversity of prey—and that a relationship between canopy and ground‐story arthropods, and their changes in abundance and composition over stand development bear further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The British Columbia study area was along the channelized South Okanagan River (McKibbin and Bishop 2010 ). Three Klamath Bird Monitoring Network (Alexander et al 2004 ; Alexander 2011 ) areas included one along the Trinity River in California (Rockwell and Stephens 2018 ) and two Oregon study areas, WIIM along the Rogue River and TOPS along the Klamath River (Rockwell et al 2017 ). The Nayarit study area consisted of openings and edges of semi-deciduous tropical forests.…”
Section: Methodsmentioning
confidence: 99%